Response of Small Traders in Traditional Markets to the Iman Portal Innovation in Avoiding Usury - Diwi Acita Irawati; Puji Astuti; Wakhid Kurniawan; Shabrina Herawati; Romi Iriandi Putra; Muhammad Yusuf Ariyadi (Postgraduate, University of Mataram, 2024)
Research on the Response of Small Traders in Traditional Markets to the Empowerment Innovation Portal Iman was carried out in Karanganyar from August to September 2023. This research aims to determine the response of small traders in traditional markets who were given socialization about Portal Iman, an empowerment innovation to avoid danger. usury. Qualitative and quantitative research was carried out in an integrated manner with surveys using questionnaires, interviews and field observations. All 92 recitation participants from 5 markets, namely Bejen, Jungke, Nglano, Jaten and Palur markets, were used as respondents for the socialization. The research results showed that the socialization participants were dominated by women (72.83%) compared to men (27.17%), with the majority aged 45 - 59 years or pre-elderly (60.87%); aged over 60 years or elderly (21.74%) and only 17.39% were aged 19 – 44 years or adults. The majority of participants' education was high school (SMA/MA/SMK) at 38.04%; Elementary school as much as 29.35% and junior high school as much as 20.65%. There were 5.44% of socialization participants who had not completed elementary school or even attended school and 6.52% who had attained higher education, either a diploma or bachelor's degree. The average length of business is 14.21 years, the longest is 44 years and the shortest is 1 year, with 66.57% own capital and 44.43% with borrowed capital, 36.67% have had contact with loan sharks, 61.11% have no contact and 2.2% did not provide information. Of the 36.6% who had contact with the loan shark, 12.22% were still in contact today, 64.44% were no longer in contact and 33.3% of respondents did not answer.